Penerapan Jig & Fixture pada Produksi Massal di Industri Manufaktur - Setiawan, Indra; Setiawan, Rohmat; Zahabiyah, Rifdah; Lestari, Tri Darma; Triantoro, Viko Wahyu; Farrel, Vincensius; H., Yoga Andriko; Puspita, Windy Yuliana (Universitas Suryakancana, 2023)
The development of the manufacturing industry in the current era of globalization is growing very rapidly as demonstrated by technological advances applied to the modern manufacturing industry. High demand from consumers requires consistency in the quantity, shape and size of a product or component to be evenly distributed in terms of quality. Other problems faced are high production costs, long processing times and unachieved productivity. In line with this, the manufacturing industry, especially mass production, requires a tool to be able to overcome these problems. Jigs & fixtures are one solution that can be used to overcome this problem. This research aims to review papers regarding the application of jigs & fixtures used in mass production systems in the manufacturing industry. This research was carried out using a systematic literature review (SLR), starting from searching, collecting, grouping and gap analysis. As a result of identifying several papers, information was obtained that jigs & fixtures can be applied to reduce production time, reduce production costs, increase productivity and improve product quality. The use of jigs & fixtures also helps reduce preparation time and allows for reduced machining time.Â Perkembangan industri manufaktur pada era globalisasi saat ini berkembang sangat pesat yang ditunjukkan dengan kemajuan teknologi yang diterapkan pada industri manufaktur modern. Tingginya permintaan dari konsumen mengharuskan konsistensi jumlah, bentuk, dan ukuran suatu produk atau komponen harus merata dari segi kualitas. Permasalahan lainnya yang dihadapi yaitu tingginya biaya produksi, waktu proses yang panjang dan produktivitas yang tidak tercapai. Sejalan dengan hal itu, industri manufaktur khususnya pada produksi massal diperlukan sebuah alat untuk dapat mengatasi permasalahan tersebut. Jig & fixture adalah salah satu solusi yang dapat digunakan untuk mengatasi masalah tersebut. Penelitian ini bertujuan untuk meninjau artikel mengenai penerapan jig & fixture yang digunakan pada sistem produksi massal di industri manufaktur beserta manfaatnya. Penelitian ini dilakukan dengan menggunakan sistematic literature review (SLR) berbasis statistik deskriptif yaitu dimulai dari penelusuran, pengumpulan, pengelompokan dan analisis kesenjangan. Hasil dari identifikasi beberapa artikel didapatkan informasi bahwa jig & fixture dapat diaplikasikan untuk mengurangi waktu produksi, mengurangi biaya produksi, meningkatkan produktivitas, dan meningkatkan kualitas produk. Penggunaan jig & fixture juga membantu mengurangi waktu persiapan dan memungkinkan pengurangan waktu permesinan.